Shape at the cross-roads: Homoplasy and history in the evolution of the carnivoran skull towards herbivory - Serrano Alarcón, Francisco José; Figueirido-Castillo, Francisco Borja; Slater, Graham; Palmqvist-Barrena, Carlos Paul (Wiley, 2010)
Patterns of skull shape in Carnivora provide examples of parallel and convergent evolution for similar ecomorphological adaptations. However, although most researchers report on skull homoplasies among hypercarnivorous taxa, evolutionary trends towards herbivory remain largely unexplored. In this study, we analyse the skull of the living herbivorous carnivorans to evaluate the importance of natural selection and phylogenetic legacy in shaping the skulls of these peculiar species. We quantitatively estimated shape variability using geometric morphometrics. A principal components analysis of skull shape incorporating all families of arctoid carnivorans recognized several common adaptations towards herbivory. Ancestral state reconstructions of skull shape and the reconstructed phylogenetic history of morphospace occupation more explicitly reveal the true patterns of homoplasy among the herbivorous carnivorans. Our results indicate that both historical constraints and adaptation have interplayed in the evolution towards herbivory of the carnivoran skull, which has resulted in repeated patterns of biomechanical homoplasy.
Keywords: Homoplasia; Evolución (Biología); Carnivora; Geometric morphometrics; Herbivory; History; Homoplasy; Skull shape